ENHANCING SECONDARY STUDENTS’ MATHEMATICAL CREATIVE THINKING THROUGH STEM PROJECT-BASED LEARNING - Ferdiansyah, Fiko; Sri Hastuti Noer; Widyastuti, Widyastuti (FKIP Universitas Muhammadiyah Prof. DR. HAMKA, 2025)
Studies have highlighted the persistently low levels of mathematical creative thinking skills among students, emphasizing the need for innovative learning interventions. The STEM-PjBL model, which integrates science, technology, engineering, and mathematics through project-based learning, offers a structured framework to enhance these skills by fostering innovative problem-solving. This study investigates the implementation of the STEM-PjBL model to improve students' mathematical creative thinking skills. A quantitative quasi-experimental approach with pre- and post-tests control group design was used, involving two purposively selected ninth-grade classes from a population of 298 students. Analysis using the Mann-Whitney U test showed a statistically significant improvement in mathematical creative thinking skills following the STEM-PjBL intervention (p < 0.05), with a normalized gain (g = 0.43), indicating that the results for the experimental group were higher than those of the control group. These findings suggest that the STEM-PjBL model is an effective strategy for improving creative thinking in mathematics education.